An Assessment of the multiple challenges associated with student’s access to electronic resources at a Public University Library in Ghana - Adzobu Armah, Nesba Yaa Anima; Cobblah, Mac-Anthony (International Journal of Knowledge Content Development & Technology, 2021)
Abstract Academic libraries strive to provide timely access to relevant electronic information resources to sundry users in the era where emerging technologies promise to revolutionise user experiences. This is seen through a host of related services and facilities packaged to provide trustworthy, convenient, and unlimited access to scholarly information resources. In developing countries, the assumption that the availability of electronic information resources necessarily translates to the accessibility of the same breaks down completely. Our understanding of how barriers to access systematically varies with the compositional and contextual characteristics of users is incomplete. Using a public university library in Ghana, this study assessed the heterogeneous barriers or constraints students encounter in accessing electronic resources based on their demographic and contextual attributes. A descriptive survey design was adopted and structured questionnaires were administered randomly to 558 students in the four constituent colleges of the University of Cape Coast, Ghana. Data were collected and analysed using SPSS and descriptive statistics were generated. The results revealed that students faced six key challenges in accessing electronic information resources in the library namely delays in the download of information, poor internet connectivity, and limited accessibility of university portal, inadequate computers in the library, poor lighting and limited ancillary services (on the spot printing facilities), with differences based on gender, academic level, and college affiliation. Only 24% males and 26% females had no challenges or problems with delays in the download of electronic information. About three-fourth of all users had poor internet connectivity and complained about inadequate computers associated with accessing electronic resources. Forty (40%) percent of undergraduate students in the colleges of education studies, agriculture and natural sciences, and humanities and legal studies each encountered four to six simultaneous challenges. Irrespective of gender, first-year undergraduate students in all four colleges were the least likely to report multiple challenges. This suggests the need for targeted and context-specific interventions to address the identified challenges. URL: http://ijkcdt.net/xml/28319/28319.pdf